Study on predicting low birth rates through data analysis on the relationship between various economic indicators and birth rates - Kim, Bong-Hyun (Edelweiss Applied Science and Technology, 2025)
In recent years, the phenomenon of declining birth rates among younger generations has been increasing due to various factors such as rising education costs, job concentration, climate change, and a preference for single living. To address this issue, the government has implemented policies that provide various incentives to encourage childbirth. However, without fundamental data analysis on birth rates, the effectiveness of these policies cannot be reliably assessed. Therefore, this paper analyzes trends in newborn births based on the population of individuals in their 20s and 30s. The analysis employs correlation techniques to examine the relationship between various economic indicators and birth rates. The data was analyzed for the interrelationship and impact among the number of marriages, number of newborns, birth rate, consumer prices, economic growth rate, and population. Through this approach, we identify key economic factors that significantly influence birth rates and explore predictions regarding low birth rates. Finally, based on the research findings, we provide insights into policies aimed at promoting childbirth.